Analisis Prediksi Kebangkrutan Suatu Perusahaan dengan Menggunakan Metode Altman Z-Scorestudi Kasus Pada PT. Garuda Indonesia Persero Tbk Periode 2008-2017 - Lian Khusnul Khotimah (Universitas Batanghari Jambi, 2019)
This research aims to look at the potential bankruptcy of PT Garuda Indonesia Tbk registered in the period 2008 to 2017 BEI by using the method of analysis of Altman Z-score revision. This research is quantitative research. Data from this research in the form of secondary data and source data taken from the Indonesia stock exchange in the form of the financial statements of PT Garuda Indonesia, Tbk period 2008 to 2017. The ratio used is X1: Working Capital to Total Assets working capital/Total assets), X2 : Retained Earning to Total Assets (Profit on hold/Total assets), X3: Earning Before Interest and Taxes (EBIT) to Total Assets (Income Before Deducting interest expense/ Total assets), the X4: Book Value of Equity to Book Value of Total Liabilities (book value the stock market/the Total value of the debt), and X5: Sales to Total Assets (Sales/Total assets). Results of the study prove that PT Garuda Indonesia Tbk in 2008-2009 condition healthy or safe with Z-Score values 4.38 and 5.07, while in 2010-2017 expressed in the Area of Grey's position evidenced by the results of the calculation of Z-Score between 1.20 and 2.90 that’s means the company is experiencing conditions bankrupt-prone to insolvency and if not promptly treated can companies into bankruptcy. The criteria the Z-Score with this categories : Z-Score < 1,20 are on potential bankruptcy category, 1,20 < Z-Score < 2,90 are on grey area category, and Z-Score > 2,90 are on non bankruptcy company.Based on the results of the study can then conclude that the methods of Altman Z score bankruptcy prediction able to answer PT Garuda Indonesia Persero Tbk for the period 2008-2017.